EFFECTIVE ORGANIZATION OF MANAGEMENT ACTIVITY ON THE BASIS OF TIME MANAGEMENT - Baybaeva Muxayyo Xudaybergenovna; Yuldasheva Khurshida Kadyrovna (Scholar Express Journal, 2021)
It is a clear fact that time is our main weapon and enemy today. It is up to each individual to use it wisely. This article discusses the organization of time management and the effective use of time
Keywords: Time Management; Management; Productivity; Superiority